2018
DOI: 10.1111/jbg.12331
|View full text |Cite
|
Sign up to set email alerts
|

Effects of incorporating environmental cost and risk aversion on economic values of pig breeding goal traits

Abstract: Economic values (EVs) of traits, accounting for environmental impacts and risk preferences of farmers, are required to design breeding goals that contribute to both economic and environmental sustainability. The objective of this study was to assess the effects of incorporating environmental costs and the risk preferences of farmers on the EVs of pig breeding goal traits. A breeding goal consisting of both sow efficiency and production traits was defined for a typical Brazilian farrow-to-finish pig farm with 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Beyond being an economic bottleneck, feed greatly contributes to the environmental impacts of pig farming (McAuliffe et al, 2016). Improvement in feed efficiency is a major goal for pig production sustainability, because it reduces environmental fluxes associated with feed production (Nguyen et al, 2011) and reduces the amount of effluent per pig as a result of mass balance (Ali et al, 2018). Feed efficiency, which is usually inversely expressed as feed conversion ratio (FCR), stands for the BW gain per unit of feed consumed.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond being an economic bottleneck, feed greatly contributes to the environmental impacts of pig farming (McAuliffe et al, 2016). Improvement in feed efficiency is a major goal for pig production sustainability, because it reduces environmental fluxes associated with feed production (Nguyen et al, 2011) and reduces the amount of effluent per pig as a result of mass balance (Ali et al, 2018). Feed efficiency, which is usually inversely expressed as feed conversion ratio (FCR), stands for the BW gain per unit of feed consumed.…”
Section: Introductionmentioning
confidence: 99%
“…As indicated by Ali et al (2018) there are few studies that analyse the implications of considering GHG emission costs in the derivation economic values for pig breeding goal traits by monetizing these emissions. Following a different approach, these authors analysed the effect of incorporating environmental cost on economic values of pig breeding goal traits considering sow efficiency and production traits.…”
Section: Resultsmentioning
confidence: 99%
“…When sow productivity traits are considered together with pig feeding traits like feed conversion ratio it has been reported that considering GHG emissions for deriving economic values reduces the importance of sow efficiency traits (Ali et al, 2018). This was not surprising because as highlighted by different studies, feed conversion ratio is one of the most important parameters influencing environmental impacts (Reckmann and Krieter, 2015), but could lead to a not clear understanding of impact of considering environmental concerns on sows productivity traits, especially using complex methodological approaches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…environmental impacts) and breeders need to include these in their breeding objectives on top of economic performance. Mitigation of environmental impacts in breeding objectives on the basis of correlated traits can be achieved by the use of EVs that incorporate environmental costs Ali et al, 2018a). As noted, more selection emphasis should be given to efficiency traits (e.g.…”
Section: Introductionmentioning
confidence: 99%